PENGARUH CITRA PERUSAHAAN TERHADAP INTENSI BELI KONSUMEN GENERASI Z: STUDI PADA PERUSAHAAN BELANJA ONLINE TOKOPEDIA - Alif Muhammad Fawwaz Zafri; Yoestini Yoestini (Diponegoro Journal of Management, 2022)
This study aims to examine the effect of corporate image on the purchase intensity of consumers specifically for Generation Z. Based on the theory of planned behavior (Ajzen, 1991), it states that three core components, namely attitudes, subjective norms, and behavioral control, together form the intensity of individual behavior. This research was conducted using a survey method on several respondents who were selected using a purposive sampling technique for users of the Tokopedia online shopping application. The respondent taken are generation Z respondents because they are the generation that is the most proficient in using gadget. The results showed that the company's image formed from corporate social responsibility activities reached by consumers, had a positive and significant effect on all core components of purchase intention. This is in line with the previous research, and indicates the importance of paying special attention to the formation of a good corporate image through corporate social responsibility activities